HIV-1 envelope facilitates the development of protease inhibitor resistance through acquiring mutations associated with viral entry and immune escape - Maphumulo, Ntombikhona F.; Gordon, Michele L. (Frontiers in Microbiology, 2024)
There is increasing evidence supporting a role for HIV-1 envelope in the development of Protease Inhibitor drug resistance, and a recent report from our group suggested that Env mutations co-evolve with Gag-Protease mutations in the pathway to Lopinavir resistance. In this study, we investigated the effect of coevolving Env mutations on virus function and structure.Co-receptor usage and n-linked glycosylation were investigated using Geno2Pheno as well as tools available at the Los Alamos sequence database. Molecular dynamics simulations were performed using Amber 18 and analysed using Cpptraj, and molecular interactions were calculated using the Ring server.The results showed that under Protease Inhibitor drug selection pressure, the envelope gene modulates viral entry by protecting the virus from antibody recognition through the increased length and number of Nglycosylation sites observed in V1/V2 and to some extent V5. Furthermore, gp120 mutations appear to modulate viral entry through a switch to the CXCR4 coreceptor, induced by higher charge in the V3 region and specific mutations at the coreceptor binding sites. In gp41, S534A formed a hydrogen bond with L602 found in the disulphide loop region between the Heptad Repeat 1 and Heptad Repeat 2 domains and could negatively affect the association of gp120-gp41 during viral entry. Lastly, P724Q/S formed both intermolecular and intramolecular interactions with residues within the Kennedy loop, a known epitope.In conclusion, the results suggest that mutations in envelope during Protease Inhibitor treatment failure are related to immune escape and that S534A mutants could preferentially use the cell-to-cell route of infection.